YES to women's ordination and NO to violence against women: Gender justice and the LWF communion of churches - Arnfríður Guðmundsdóttir (Dialog, 2024)
Gender justice has been a priority of the Lutheran Word Federation (LWF) for decades, much longer than the existence of its Gender Justice Policy (2013) where it is affirmed that gender justice is “a matter of faith.” The LWF has always put great emphasis on the theological problems gender justice issues present, as opposed to an assessment that women's experiences of exclusion and abuses of power are strictly acknowledged and treated as human rights violations. Therefore the committment to gender justice has been strongly tied to the importance of theological education as a critical tool against misleading theologies that justify patriarchal world views, including traditional gender roles and women's submissiveness. The focus in this article is on two major gender justice issues the LWF has called particular attention to, namely women's equal participation to men in leadership roles, including ordained ministry, and violence against women within the church and society at large. Ever since the Seventh Assembly of the LWF in Budapest in 1984, LWF member churches have been urged in assembly messages and resolutions to promote full inclusion of women in the life of church and society and to secure their health and well-being. Multiple documents, action plans, policies, and reports have been written in order to follow up on the directions from the assemblies regarding women. My aim here is to explore those documents and to lift up what has already been said about women's leadership roles in church and society and about discrimination and violence against women. These documents laid the groundwork for what was stated in the documents passed at the Thirteenth Assembly of the LWF in Poland in September 2023.